Death in a strange country - Leon, Donna (New York : Chapmans publishers, 1993)
Early one morning, a sleepy Brunetti confronts a grisly sight, the bloated body of a young man fished out of a fetid Venetian canal. The corpse turns out to be that of an American soldier who was stationed at the U.S. Army post in Vicenza, near Venice. Brunetti$1 (Bs foppish, media-conscious boss likes his cases tied up quickly in the neatest packages possible, and he pressures Brunetti to declare the death drug-related and leave it at that. But the thoroughly spotless life of the deceased and the rarity of drug-related crime in Venice make Brunetti doubt his superior$1 (Bs advice even more than usual. Throwing protocol to the winds, Brunetti scours the base at Vicenza for clues. The suspicious "suicide" of a colleague of the dead soldier and a little boy$1 (Bs rash point Brunetti toward toxic waste dumping and an insidious cover-up that extends from the Mafia to the U.S. Army to the police and perhaps even to Brunetti$1 (Bs own family. Two people have already been killed for trying to expose this cabal. Will Brunetti be the third?" "Leon$1 (Bs portrayals of Venice and the Army base - an improbable island of Bermuda shorts and Baskin-Robbins in the Italian countryside - are consistently fascinating. Most memorable, though, is her depiction of Brunetti. As a devoted family man and pillar of the community who quietly abhors the powers that be, he is original, subtly drawn, and completely irresistible."--BOOK JACKET.s
Keywords: Brunetti, Guido (Fictitious character) -- Fiction; Police -- Italy -- Venice -- Fiction; Americans -- Italy -- Fiction; Venice (Italy) -- Fiction; Detective and mystery stories